Social skills in primary education: Influential variables in intercultural contexts - Vega, Eva Maria Aranda; Fernandez, Maria Tome; Marcos, Jose Manuel Ortiz (Journal of Education and e-Learning Research, 2024)
This study examined the most common social skills among elementary school students in an intercultural environment with contextual diversity, taking age, gender and place of birth into consideration. A total of 803 students (aged 6 to 12) were assessed using the previously validated “social skills questionnaire for intercultural students in primary education”. Data were analyzed by descriptive and comparative statistics using the most recent version of SPSS software taking into account sociodemographic variables about social skills. The results indicate that gender exhibits different levels of social skills. Specifically, boys present higher scores than girls to reject and end interactions as well as in the ability to make suggestions to others. Students' social skill development is influenced by their nationality since social interaction within a community and the development of specific social skills are determined by the traditions and customs of every country. It is necessary to consider the diverse profiles of students as priority targets for educational interventions aimed at fostering these types of skills which will contribute to social integration in diverse contexts. The practical implications of this study suggest that educational programs should be adapted to address gender and nationality differences in the development of social skills. Better social and cultural integration in diverse school environments help students interact effectively and develop essential social competencies in a globalized world.